Transformasi Marketing Mimuman Lokal Bebasis Digital pada Usaha Produksi Moke - Bading, Akarinus; kopong, Rivarno; Kwure, Ipang; sega, Celmand (INCOME: Indonesian Journal of Community Service and Engagement, 2023)
Abstract This Community Service Activity (PKM) aims to provide assistance to local MSME beverage business actors in the moke production business in terms of implementing digital-based marketing strategies with the methods used in this PKM being e-learning and packaging training in the form of a platform (Facebook Marketplace) as marketing facilities and packaging innovation are expected to be able to increase sales of local drinks which are still very commonly used by business actors in achieving increased sales production in the form of training in implementing digital-based marketing strategies and have been implemented with the activity participant being Mr Silverster Sola as a moke production business actor in the village Watugong, Brai Hamlet. The results obtained from this activity are the interpretation of digital-based marketing strategies in moke production businesses that are able to have a positive impact on local beverage businesses.